2019
DOI: 10.1038/s41598-019-53111-7
|View full text |Cite
|
Sign up to set email alerts
|

Improved power and precision with whole genome sequencing data in genome-wide association studies of inflammatory biomarkers

Abstract: Genome-wide association studies (GWAS) have identified associations between thousands of common genetic variants and human traits. However, common variants usually explain a limited fraction of the heritability of a trait. A powerful resource for identifying trait-associated variants is whole genome sequencing (WGS) data in cohorts comprised of families or individuals from a limited geographical area. To evaluate the power of WGS compared to imputations, we performed GWAS on WGS data for 72 inflammatory biomar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 49 publications
1
68
0
Order By: Relevance
“…When such a variant was found, conditional analysis was performed and the novelty status updated accordingly. We further incorporated evidence from three association studies with signals that were not reported in the GWAS catalog [40][41][42] . Using this method, there were thirty-nine proteins measured in this study for which we were not able to find evidence of previous studies of genetic associations.…”
Section: Methodsmentioning
confidence: 99%
“…When such a variant was found, conditional analysis was performed and the novelty status updated accordingly. We further incorporated evidence from three association studies with signals that were not reported in the GWAS catalog [40][41][42] . Using this method, there were thirty-nine proteins measured in this study for which we were not able to find evidence of previous studies of genetic associations.…”
Section: Methodsmentioning
confidence: 99%
“…Instead of using imputed genotype data, Höglund et al used whole genome sequencing data to carry out genome-wide association studies (GWAS) on the levels of 72 inflammatory proteins. This led to the identification of 18 novel loci that were not identified using genotyped or imputed SNPs [36]. A number of studies have also carried out epigenome-wide association studies (EWAS) on the levels of a small set of inflammatory proteins, including C-reactive protein, interleukins-(1β, 4, 6, 9 and 10), interferon-gamma, transforming growth factor-beta and tumour necrosis factor [37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…In a study published by Hoglund et al 72 inflammatory biomarkers were analyzed and 18 novel associations were identified when using GWAS approach on WGS data, that were not detected when analyzing the same biomarkers with genotyped or imputed SNPs. This study suggests that we can enhance the power and accuracy of GWAS when using WGS data by having the ability to identify quantitative trait loci and nucleotides (QTNs) [ 31 , 32 ]. A few programs, including the Consortium of Asthma in African Populations of the Americas (CAAPA) and the Trans-Omics for Precision Medicine program (TOPMed) have begun using WGS, and several CNVs, structural variants, and rare coding variants have already been identified [ 33 , 34 , 35 ].…”
Section: Genetics In Asthmamentioning
confidence: 99%